Seroprevalence and Associated Factors of SARS CoV-2 Antibodies among employees of IMDC and its teaching hospital - Farah Rashid , Sadia Zafar , Usman Zafar , Nadia Tariq , Khalid Hassan, (Journal of Rawalpindi Medical College, 2021)
Abstract: Background: Since the emergence of COVID-19 in Wuhan, China, it has claimed many lives and global economic losses. Healthcare workers have been the most exposed group in this pandemic. This study aims to determine the prevalence of anti-SARS-CoV-2 antibodies among the employees of Islamabad Medical and Dental College and its allied hospital Akbar Niazi Teaching Hospital. Methodology: All members of the staff and faculty of Islamabad Medical and Dental College and allied hospital Akbar Niazi Teaching Hospital were encouraged to get tested for SARS-CoV-2 antibodies and 294 employees volunteered for the study from 23rd July to 30th July,2020 through Elecsys® Anti-SARS-CoV-2 (Immunoassay for the qualitative detection of IgG antibodies against SARS-CoV-2 in human serum and plasma). Results: Out of 284 volunteers, 87 (30.6%) were SARS-CoV-2 antibody positive, with the mean antibody level in seropositive individuals recorded as 24.4418 ± 25.3494. , housekeeping and sanitary workers were the most affected; 14 (48.3%) were antibody positive, while 15 (51.7%) were antibody negative. After housekeeping and sanitary staff, the second most affected workers were lab technicians (37.1% were positive compared to 62.9% negative). Fever, loss of taste or smell and breathing difficulty were the most significantly associated symptoms with COVID-19 antibody seroprevalence as suggested by the p values 0.003, 0.004 and 0.032 respectively. Out of the 13 PCR positive participants (in the preceding 3 months) 10 (76.9%) showed positive antibody in their serum and 3 (23.1%) had not developed antibodies. Conclusion: Seroprevalence of SARS-CoV-2 antibodies was estimated to be high among the healthcare staff (30.6%), with the housekeeping and sanitary staff to be the most affected employees, probably due to the breach of personal protection. Fever, loss of taste or smell and breathing were strongly associated with seropositivity of SARS-CoV-2 antibodies. Key Words: SARS-CoV-2, antibody testing, Covid-19, healthcare workers